2003
DOI: 10.1073/pnas.1533026100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an activator protein required for the induction of fruA , a gene essential for fruiting body development in Myxococcus xanthus

Abstract: Myxococcus xanthus exhibits social behavior and multicellular development. FruA is an essential transcription factor for fruiting body development in M. xanthus. In the present study, the upstream promoter region was found to be necessary for the induction of fruA expression during development. A cis-acting element required for the induction was identified and was located between nucleotides ؊154 and ؊107 with respect to the transcription initiation site. In addition, it was found that two binding sites exist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
121
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(126 citation statements)
references
References 39 publications
(50 reference statements)
4
121
1
Order By: Relevance
“…MrpC is similar to CRPfamily transcription factors and was shown previously to be essential for development (20). A form of MrpC lacking the N-terminal 25 residues, called MrpC2, was identified previously in an AS fraction based on binding to the fruA promoter region (24). Our results suggested that MrpC2 in the AS fraction binds to the fmgA promoter region at a site (Ϫ63 to Ϫ46) important for promoter activity.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…MrpC is similar to CRPfamily transcription factors and was shown previously to be essential for development (20). A form of MrpC lacking the N-terminal 25 residues, called MrpC2, was identified previously in an AS fraction based on binding to the fruA promoter region (24). Our results suggested that MrpC2 in the AS fraction binds to the fmgA promoter region at a site (Ϫ63 to Ϫ46) important for promoter activity.…”
supporting
confidence: 64%
“…Cooperative binding of FruA and MrpC2 to the fmgA promoter region and other promoter regions, together with activation of fruA transcription by MrpC2 (24), represents a coherent feed-forward regulatory loop design found commonly in regulatory networks because of its beneficial characteristics (38). C-signaling could affect production of MrpC2 and/or activity of FruA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of fruA is developmentally regulated, dependent on A-and E-signals, and initiates at 6 h after the onset of development. Recently, a fruA promoter-binding protein was isolated from developmental cell extracts by using a DNA binding assay with the DNA fragment containing the upstream region of the fruA promoter (9). Based upon its partial sequence, this fruA promoter-binding protein was found to be identical to MrpC, which belongs to the cyclic AMP receptor protein family of transcriptional regulators (9).…”
Section: Fruiting Body Development In Myxococcus Xanthus Is a Multicementioning
confidence: 99%